Efektivitas Kegiatan Membentuk Bubur Koran Terhadap Kemampuan Motorik Halus Anak Usia 4-5 Tahun - Azizah Azahra; Rista Dwi Permata (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECTIVENESS OF NEWSPAPER PULP FORMING ACTIVITIES ON THE FINE MOTOR SKILLS OF CHILDREN AGED 4-5 YEARS The purpose of this study was to determine the effectiveness of newspaper pulp forming activities in improving fine motor skills in children aged 4 to 5 years. This study applied a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research subjects consisted of children in Group A at TK PGRI Prunggahan Kulon, who were divided into two groups, namely the experimental group and the control group. The experimental group received treatment in the form of newspaper pulp forming activities, while the control group received regular classroom learning. Data were collected through observation, documentation, and a research instrument in the form of a pretest-posttest observation sheet for children’s fine motor skills. The data were analyzed using descriptive statistics, normality testing, homogeneity testing, and hypothesis testing through the t-test. The findings showed that the fine motor skills of children in the experimental group improved after participating in newspaper pulp forming activities. This improvement was shown by the difference between pretest and posttest scores and by the result of hypothesis testing, which showed a significance value of 0.000 < 0.05. This indicated that newspaper pulp forming activities were effective in improving the fine motor skills of children aged 4 to 5 years. These activities trained eye-hand coordination, finger strength, hand flexibility, and movement control through several activities, such as tearing, squeezing, grasping, pressing, and twisting. Therefore, newspaper pulp forming activities could be used as an alternative creative learning activity to stimulate fine motor development in early childhood.